2015
DOI: 10.5194/npg-22-473-2015
|View full text |Cite
|
Sign up to set email alerts
|

Search for the 531-day-period wobble signal in the polar motion based on EEMD

Abstract: Abstract. In this study, we use a nonlinear and nonstationary time series analysis method, the ensemble empirical mode decomposition method (EEMD), to analyze the polar motion (PM) time series (EOP C04 series from 1962 to 2013) to find a 531-day-period wobble (531 dW) signal. The 531 dW signal has been found in the early PM series (1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977), but cannot be found in the recent PM series (1978-2013) using conventional analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Wahr (1983) implied that there exists an 18-month (∼ 547day) polar wobble (which can be considered as coinciding with the 531 dW signal mentioned in the present paper), which could be caused by oceanic excitation. Chen et al (2010) further demonstrated that the atmospheric excitation may give rise to the 531 dW signal with an amplitude 15 mas using the atmospheric angular momentum (AAM) data set spanning from 1948 to 2006. But, from the above results, those excited 531 dW signals almost disappear from the 1978-1994 and 1995-2013 series.…”
Section: Results From the Pm Series With/without Using Eemdmentioning
confidence: 95%
See 4 more Smart Citations
“…Wahr (1983) implied that there exists an 18-month (∼ 547day) polar wobble (which can be considered as coinciding with the 531 dW signal mentioned in the present paper), which could be caused by oceanic excitation. Chen et al (2010) further demonstrated that the atmospheric excitation may give rise to the 531 dW signal with an amplitude 15 mas using the atmospheric angular momentum (AAM) data set spanning from 1948 to 2006. But, from the above results, those excited 531 dW signals almost disappear from the 1978-1994 and 1995-2013 series.…”
Section: Results From the Pm Series With/without Using Eemdmentioning
confidence: 95%
“…The spectra of synthetic series V (e) and VI (f); and the spectra of the IMF5 and IMF6 of synthetic series VI after using EEMD (f1-f3). and Chen et al (2010) suggested, the 531 dW can be excited by atmospheric/oceanic effects, and the excited signal by atmospheric or oceanic effects can be found in the PM se-ries only after convoluting with the CW term. However, the 531 dW signals excited by atmospheric and oceanic effects seem to have different phases; hence, the 531 dW cannot be found in the PM series (Chen et al, 2010).…”
Section: Results From the Sg Recordsmentioning
confidence: 99%
See 3 more Smart Citations